PENGARUH KEDISIPLINAN, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. ADI RAYA CONSTRUCTION GRESIK - Alfiani Rosyadah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
The purpose of this study to determine the influence of discipline, compensation and organizational culture on employee performance at PT. Adi Raya Construction Gresik. The sample used proportionate stratified random sampling technique with 77 employee sampling using krejcie table with error size 5%. Data analysis techniques use multiple linear regression. Results of multiple linear regeresis proves that discipline, compensation and organizational culture is shown to have a partially significant effect on the performance of employees of PT. Adi Raya Construction Gresik. These results can be interpreted that the existence, discipline, compensation and organizational culture that has been applied to improve employee performance in PT. Adi Raya Construction Gresik.